Stanislavsky's system as an enactive guide to embodied cognition?. Issue 1 (2nd January 2017) - Clare, Ysabel
ABSTRACT: This paper presents a model of the structure of subjective experience derived from the work of Konstantin Stanislavsky, and demonstrates its usefulness as a functional framework of enacted cognitive embodiment by using it to articulate his approach to the process of acting. Research into Stanislavsky's training exercises reveals that they evoke a spatial adpositional conceptualisation of experience. When reflected back onto the practice from which it emerges, this situates the choices made by actors as contributing towards the construction of a stable attention field with which they enter into relationship during performance. It is suggested that the resulting template might clarify conceptual distinctions between practices at the unconscious level, and a brief illustrative comparison between Stanislavsky's and Meisner's practices is essayed. A parallel is drawn throughout with the basic principles of embodied cognition, and correlations found with aspects of Dynamic Field Theory and Wilson's notions of "on-" and "off-line" processing.